THE EFFECT OF PASTEURIZATION STAGE ON THE PRODUCTION OF STRAW MUSHROOM (VOLVARIELLA VOLVACEA, BULL. EX. FR./SING.) - Jessica Elfani Bermuli; Wahyu Irawati; Reisky Megawati Tammu (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2022)
God created Indonesia with a tropical climate that is very appropriate to support the development of straw mushroom cultivation (Volvariella volvaceae). One of the stages of mushroom cultivation sequentially is pasteurization. This study aims to determine the effect of pasteurization stages, the accuracy of the pasteurization temperature, and the factors that influence the growth of straw mushrooms. The method in this study was carried out using livestock manure, with a composition of 400 gr goat manure and 500 gr rabbit manure. The pasteurization stage is maintained at a temperature of 60-700C with a humidity of 80-90%. The watering interval at the observation stage was 4 days with a frequency of 40% in experiment 1 and every day or a frequency of 100% in experiment 2. The results showed that the pasteurization stage was very influential on the mushroom growing media. Inaccuracy in pasteurization resulted in many weeds that thrived, thus inhibiting the growth of straw mushrooms. The optimal temperature in the pasteurization stage is 60-900C. The factors that influence the growth of mushroom are the selection of materials as fertilizers for mushroom cultivation, temperature, humidity include interval and frequency of watering, pasteurization process, weeding the contaminants, and time of observation.